Clay art with Gloria Elliott - Canizares, Susan (New York : Scholastic, 1999)
Shows how Gloria Ellito uses clay to make sculptures, mobiles, music boxes, necklares, and finger puppets.
Keywords: Pottery craft -- Juvenile literature; Handicraft